Statistical models for concrete containing wood chipping as partial replacement to fine aggregate - Mohammed, B.S. (2014)
The properties of concrete containing wood chippings as partial replacement to fine aggregate are presented in this paper. Wood chipping was treated by water before mixing to prevent it from soaking the water meant for cement hydration. Fifteen trial mixes were prepared and cast using three water-cement ratios (0.37, 0.41 and 0.57) at different replacement levels of wood chippings. Fresh concrete properties tested included slump, unit weight and air content. Hardened concrete properties tested included compressive strength, splitting tensile strength, flexural strength, modulus of elasticity, rebound hammer (RH) and ultrasonic pulse velocity (UPV). Several statistical models were developed to show the relationships between measured responses and variables and among measured responses. These models were validated using various model statistics. Test results show that disposal of wood chipping in concrete is feasible and appropriate. These models are providing a design mix aid of concrete containing wood chipping as partial replacement of fine aggregate. Â© 2014 Elsevier Ltd. All rights reserved.